2015
DOI: 10.1039/c5ra13822a
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of surface bio-functionality by using gold nanostructures on protein repellent surfaces

Abstract: The integration of gold nanoparticles (Au NPs) or nanostructures on solid surfaces for developing nanostructured biointerfaces has become a major research topic in the field of nanobiotechnology in particular for the development of a new generation of multifunctional bioanalytical platforms. This has led to considerable research efforts for developing quick and direct nanofabrication methods capable of producing well-ordered 2D nanostructured arrays with tunable morphological, chemical and optical properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Furthermore, due to the nonadhesive properties of the PEO‐based surface, the results showed that the AuNPs selectively interacted with the cells and were selectively functionalized with bioactive molecules. This demonstrates that AuNP patterns can potentially be used as cell‐ and protein‐ affinity‐based biosensors to study protein–nanoparticle and cell–nanoparticle interactions . Similar results have been reported by Li et al, who coated a silicon oxide (SiO 2 ) substrate surface with cell‐repellent (as background coating) and cell‐adhesive ligands (immobilized on AuNPs) to tune neuron adhesion and alignment.…”
Section: Biomedical Applications Of Functional Nanomaterials On 2d Susupporting
confidence: 80%
“…Furthermore, due to the nonadhesive properties of the PEO‐based surface, the results showed that the AuNPs selectively interacted with the cells and were selectively functionalized with bioactive molecules. This demonstrates that AuNP patterns can potentially be used as cell‐ and protein‐ affinity‐based biosensors to study protein–nanoparticle and cell–nanoparticle interactions . Similar results have been reported by Li et al, who coated a silicon oxide (SiO 2 ) substrate surface with cell‐repellent (as background coating) and cell‐adhesive ligands (immobilized on AuNPs) to tune neuron adhesion and alignment.…”
Section: Biomedical Applications Of Functional Nanomaterials On 2d Susupporting
confidence: 80%
“…These patterned and nanostructured surfaces have then been tested for protein bio-recognition analysis, using QCM-D in flow mode, and as a cell culture platform. 51 These surfaces could become an ideal platform to study protein-nanoparticle and cell-nanoparticle interactions using affinity-based biosensors like QCM but also SPR (or LSPR) due to the metallic nature of nanoparticles.…”
Section: Surface Functionalization For Multiplex Cell Screeningmentioning
confidence: 99%
“…The emergence of microfluidic organ-on-a-chip systems and the ongoing efforts to mimic live organ physiology on a smaller scale led to renewed interest in the optimal conditions needed to support a cell’s culture in an artificially designed microenvironment 1 2 3 . The sub-micrometer feature resolution and accurate geometries that can be readily manufactured using soft lithography opened new frontiers towards the identification of optimal conditions to support such conditions 4 5 .…”
mentioning
confidence: 99%